Circularly Polarized Luminescence and Coordination Geometries in Mononuclear Lanthanide(Iii) Complexes - Aravena-Ponce, D; Aravena-Ponce, D; Llanos-Silva, L; Llanos-Silva, L (Elsevier B.V., 2024)
The interest in chirality crosses many research areas in chemistry, physics, materials, and life sciences. Besides the fundamental importance of chiral recognition in biological systems, the exploitation of chirality offers an additional degree of freedom to broaden the perspective for new functional materials. From a spectroscopic point of view, the signature property of chiral systems is their different absorption/emission intensity for left- and right- handed circularly polarized light. This difference is called dissymmetry and can be measured for both absorption (gabs in circular dichroism) and emission (glum in circularly polarized luminescence) experiments. Among inorganic systems, lanthanide complexes hold the maximum values for glum due to their unique interplay between magnetic and electric dipole mechanisms, characteristic for f-f transitions. In this review, we provide an overview of important chemical families of mononuclear lanthanide complexes associated with strong circularly polarized emission dissymmetry, as this property is fundamentally connected with the chiral environment around the lanthanide ion. In the final section, presented systems are analyzed in terms of their coordination number, geometry, and distortion with respect to reflection with the aid of Continuous Symmetry and Shape Measurements. © 2024 Elsevier B.V.